Drought in Afghanistan: Exploring the vulnerability and drought coping capacity of the farmers of Arabmazari village, Chamtal district, Balkh Province, Afghanistan - Faizi, Meena; Maryono, Maryono; Hermawan, Ferry (Journal of Bioresources and Environmental Sciences, 2024)
Drought is one of the impacts of climate change, which affects agriculture's productivity and, eventually, farmers in Afghanistan. Afghanistan has a typical inland continental climate with considerable temperature and precipitation variation between seasons. A considerable part of Arabmazari's village relies on irrigation for agriculture; however, with the low precipitation, temperature rise, and surface and groundwater depletion, farmers experiences drought. The objective of the research is to explore the vulnerability and coping capacity of the farmers of Arabmazari village to drought. The research considers a non-probability purposive sampling method. The data was collected from 3 members of the Ministries through interviews and from around 30 farmers through FGD and questionnaires. The research adopts descriptive and correlational statistics to assist with the qualitative and quantitative nature of the study. The research finds that farmers are generally highly vulnerable to drought impacts. With the government's lack of facilities, financial capacity, and absence of mitigation and preparatory measures, farmers are forced to rely on their own, often ancient, methods to plan and survive drought. Some coping strategies for crops and livestock included cultivating drought-resistant crops, changing cropping patterns, practicing crop rotation, soil treatment, and providing supplementary feeds for animals. Non-farm coping strategies were selling/pledging assets, migration, seeking employment elsewhere, dropping out of school, and seeking humanitarian aid. The government intervention was only through drought relief, which was ineffective in the long run. It is recommended that the government intervention adopt more effective mitigation and preparatory measures. Moreover, a thorough research/survey is to be done to find out the responsibilities and contribution of the Water Association Committee of Chamtal district towards the farmers of Arabmazari village. Currently, a cost-effective and immediate adaption is a practical option for the farmers, such as GIS, to create a localized map of the drought-prone areas.